Women and Money: Unique Issues - Finances in a Divorce - Lynda Spence; Martie Gillen; Diann Douglas (EDIS, 2013)
Separation and divorce impact family financial management on multiple levels. Women going through a divorce will have reduced resources and the added expenses of the divorce process. If you are going through a divorce, you should carefully examine the financial factors listed in this publication. Also, you should know that sensible planning may help to lessen the financial stress associated with the transition from marriage to divorce. This 7-page fact sheet was written by Lynda Spence, Martie Gillen, and Diann Douglas, and published by the UF Department of Family Youth and Community Sciences, January 2013.